Negotiating Authority and Knowledge: Religion, Science, and Politics in the Fatwa Transformations of the Indonesian Ulema Council - Aseri, Mukhsin; Rasyid, Muhammad; Mustapha, Ahmad Sharifuddin bin; Aseri, Akh. Fauzi; Fedorchenko, Oleh (Journal of Islamic Law, 2025)
This article examines the dynamics of Islamic legal thought in Indonesia as reflected in the fatwas issued by the Indonesian Ulema Council (Majelis Ulama Indonesia, MUI) on issues of worship, science, and technology. While Islamic law is often perceived as a product of normative, text-based interpretation, in practice it has undergone significant transformation through its interaction with scientific innovation and socio-political contexts. Existing scholarship has tended to address the normative, scientific, or political dimensions separately, without adequately exploring their intersections. This article aims to identify patterns of change in MUI’s fatwas and to explain how the dialectic among scriptural interpretation, institutional authority, modern science, and state policy has shaped these transformations. Employing a qualitative, library-based methodology, the research analyzes nine fatwas issued between 1975 and 2024 on four key issues—vasectomy, meningitis vaccination, qibla orientation, and lunar calendar calculation—within the framework of the sociology of knowledge. The findings reveal three main patterns of transformation: the relaxation of previously strict rulings, the annulment of earlier fatwas, and the refinement of legal norms. These shifts were driven by new scientific evidence (such as post-vasectomy recanalization, the development of halal vaccines, and modern astronomical methods), social pressures (public health imperatives and the need for religious unity), and political considerations (alignment with state policies). Accordingly, MUI’s fatwas should be understood not merely as products of normative ijtihād (legal reasoning) but as social constructions negotiated at the intersection of religious authority, scientific legitimacy, and political interests. These transformations highlight the MUI’s efforts to maintain the relevance of Islamic law in the face of modernity's challenges and rapid scientific advancements. [Artikel ini membahas dinamika pemikiran hukum Islam di Indonesia sebagaimana tercermin dalam fatwa-fatwa Majelis Ulama Indonesia (MUI) terkait isu ibadah, sains, dan teknologi. Selama ini, hukum Islam kerap dipahami sebagai produk penafsiran normatif berbasis teks, padahal dalam praktiknya ia mengalami transformasi signifikan melalui interaksi dengan inovasi ilmiah dan konteks sosial-politik. Kajian sebelumnya cenderung memisahkan dimensi normatif, ilmiah, atau politis, tanpa menelaah secara komprehensif persinggungan di antara ketiganya. Artikel ini bertujuan mengidentifikasi pola perubahan dalam fatwa MUI sekaligus menjelaskan bagaimana dialektika antara penafsiran keagamaan, otoritas institusional, sains modern, dan kebijakan negara membentuk transformasi tersebut. Dengan menggunakan metodologi kualitatif berbasis studi pustaka, penelitian ini menganalisis sembilan fatwa yang diterbitkan antara 1975–2024 terkait empat isu utama—vasektomi, vaksin meningitis, arah kiblat, dan penentuan awal bulan kamariah—dalam kerangka sosiologi pengetahuan. Temuan dalam artikel menunjukkan tiga pola utama perubahan: pelonggaran ketentuan yang semula ketat, pembatalan fatwa sebelumnya, dan penyempurnaan norma hukum. Pergeseran ini dipicu oleh bukti ilmiah baru (seperti kemungkinan rekanalisasi pasca-vasektomi, hadirnya vaksin halal, serta metode astronomi modern), tekanan sosial (kebutuhan kesehatan publik dan persatuan umat), serta pertimbangan politik (dukungan terhadap kebijakan negara). Dengan demikian, fatwa MUI tidak semata-mata dipahami sebagai hasil ijtihad normatif, melainkan sebagai konstruksi sosial yang lahir dari negosiasi antara otoritas agama, legitimasi sains, dan kepentingan politik. Transformasi ini menegaskan upaya MUI untuk menjaga relevansi hukum Islam di tengah tantangan modernitas dan percepatan kemajuan sains.]